Microbes-mediated synthesis strategies of metal nanoparticles and their potential role in cancer therapeutics. (November 2022) - Khalil, Ali Talha; Ovais, Muhammad; Iqbal, Javed; Ali, Arbab; Ayaz, Muhammad; Abbas, Manzar; Ahmad, Irshad; Devkota, Hari Parsad
Abstract: Past few years have seen a paradigm shift towards ecofriendly, green and biological fabrication of metal nanoparticles (MNPs) for diverse nanomedicinal applications especially in cancer nanotheranostics. Besides, the well-known green synthesis methods of plant materials, the potential of the microbial world (bacteria, fungi, alga, etc.) in biofabrication is equally realized. Biomolecules and enzymes in the microbial cells are capable of catalyzing the biosynthesis process. These microbial derived inorganic nanoparticles have been frequently evaluated as potential agents in cancer therapies revealing exciting results. Through, cellular and molecular pathways, these microbial derived nanoparticles are capable of killing the cancer cells. Considering the recent developments in the anticancer applications of microbial derived inorganic MNPs, a dire need was felt to bring the available information to a single document. This manuscript reviews not only the mechanistic aspects of the microbial derived MNPs but also include the diverse mechanisms that governs their anticancer potential. Besides, an updated literature review is presented that includes studies of 2019-onwards.